Characteristics for success in elite junior and senior swimmers - Dunman, N.; Morris, J.; Nevill, M.; Peyrebrune, M. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study was to describe and compare key anthropometric, physiological and socio-demographic characteristics of junior and senior elite swimmers at two performance levels and to determine the importance of these attributes to successful swimming performance. Sixty-five (34 males and 31 females) senior and 561 (305 males and 256 females) junior elite swimmers undertook a battery of anthropometric and physiological tests, and additional family back-ground assessment. The combination of variables was able to differentiate between the two levels of senior performance in males (P<0.05). Significant predictors of swimming performance (P<0.05) differed from junior to senior level in both males and females. A longitudinal approach is required to track the importance of certain characteristics during growth and development.